(untitled) (Global Journal of Medical Research, 2018)
Soft tissue sarcomas account for 1% of all neoplasms, with the second commonest being liposarcomas. Liposarcomas in the popliteal fossa often grows to a large size, as neither the patient nor the clinician will initially be able to palpate the tumour due to its depth in the tissues and the fact that the tumour is often low grade. Its size often does not facilitate the ability to resect the mass with wide margins. The following article discusses prognostic factors for liposarcomas with regards to histological subtype, anatomical distribution, resection margins and neoadjuvant therapy.